2018
DOI: 10.1016/j.ymeth.2017.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Determining mRNA half-lives on a transcriptome-wide scale

Abstract: Every step in the life cycle of an RNA transcript provides opportunity for regulation. One important aspect of post-transcriptional control is the regulation of RNA stability. Of the many strategies for determining mRNA stability, transcription inhibition and metabolic labeling have proved the most amenable to high-throughput analysis and have opened the door to dissecting mRNA decay transcriptome-wide. Here, we describe experimental and computational methods to determine transcriptome-wide RNA stabilities usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 44 publications
0
69
0
Order By: Relevance
“…Previous studies have provided evidence that the act of transcription may play a role in shaping chromatin organization [26,27,29,30,34,35], yet the global consequences of complete transcriptional arrest (i.e., blocking all three polymerases) on mammalian chromosomal architecture are not well understood. Accordingly, to assess whether genome organization is affected differently by the act of transcription compared to loss of steady-state RNA following RNase treatment, we treated K562 cells with actinomycin D (ActD), a drug that quickly (i.e., within 24 h) and irreversibly inhibits all polymerases and results in complete transcriptional arrest [36][37][38] ( Fig 1C). Agarose gel electrophoresis analysis of total RNA extracted from the same number of cells as controls upon 24 h of ActD treatment revealed that~50% of the 28S/18S ribosomal RNA bands remain, indicating the inhibition of global transcription and a decrease in nuclear RNA content ( Fig 1D).…”
Section: Experimental Strategy and Characterization Of Rnase Treatmenmentioning
confidence: 99%
“…Previous studies have provided evidence that the act of transcription may play a role in shaping chromatin organization [26,27,29,30,34,35], yet the global consequences of complete transcriptional arrest (i.e., blocking all three polymerases) on mammalian chromosomal architecture are not well understood. Accordingly, to assess whether genome organization is affected differently by the act of transcription compared to loss of steady-state RNA following RNase treatment, we treated K562 cells with actinomycin D (ActD), a drug that quickly (i.e., within 24 h) and irreversibly inhibits all polymerases and results in complete transcriptional arrest [36][37][38] ( Fig 1C). Agarose gel electrophoresis analysis of total RNA extracted from the same number of cells as controls upon 24 h of ActD treatment revealed that~50% of the 28S/18S ribosomal RNA bands remain, indicating the inhibition of global transcription and a decrease in nuclear RNA content ( Fig 1D).…”
Section: Experimental Strategy and Characterization Of Rnase Treatmenmentioning
confidence: 99%
“…For mRNA, experimentally measured half-lives usually lie in the range of seconds to hours (61)(62)(63)(64). Protein half-lives are usually longer than mRNA half-lives (65) and lie between hours and days (63,66).…”
Section: Parameter Valuesmentioning
confidence: 99%
“…However, RNA-seq represents a static image of the process of transcription, while biological processes are by their very nature dynamic. Recent studies on transcriptome dynamics have shown that transcript stability is correlated with function [3][4][5][6]. For instance, transcription factor mRNAs have high average decay rates [6] and mRNA turnover correlates with signaling pathways active in cancer, suggesting a post-transcriptional component to oncogenesis [7].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, understanding transcriptional dynamics is important for understanding disease pathogenesis including in cancer. mRNA decay studies have traditionally been dominated by the use of transcriptional inhibitors such as actinomycin D [8,4] -amanitin [3,9] to arrest transcription. mRNA concentrations are then quantified at progressive time points after transcriptional arrest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation